Sobre a influência dos centralizadores dos automorfismos de ordem dois em grupos de ordem ímpar - Rojas, Yerko Contreras (2013)
This document presents an approach and development of some of the results of Shumyatsky in [14, 15, 16, 17, 18], where he worked with automorphisms of order two in finite groups of odd order, mainly showing the influence that the structure of the centralizer has on that of Group. Let G be a group with odd order, and ϕ an automorphism on G, of order two, where G = [G,ϕ], and given a limitation in the order of the centralizer of ϕ regard to G, CG(ϕ), which induces a limitation in the order of derived group G′ of group G, and we also verified that G has a normal subgroup H that is ϕ-invariant, such that H′ ≤ Gϕ and its index [G : H] is bounded with the initial limitation. With the same hypothesis of the group G and with the same limitation of the order of the centralizer of the automorphism, let V a abelian p-group such that G⟨ϕ⟩ act faithful and irreductible on V, then there is a bounded constant k, limitated by a function depending only on the parameter m, where m is tha limitation in the order of CG(ϕ), and elements x1, ...xk ∈ G−ϕ such that V = ρϕx 1,...,xk(V−ϕ).